Upaya Meningkatkan Hasil Belajar PKn Pokok Bahasan Politik Luar Negeri Indonesia Pada Siswa Kelas VI SD Negeri 001 Kecamatan Bangun Purba - Edison Edison (STKIP Rokania Pasir Pangaraian, 2018)
National education should be able to cultivate and deepen the love of the homeland, strengthen the spirit of nationalism and sense of social solidarity. This study aims to provide information / information for Civics teachers about the development of inquiry methods in learning Civics in Class VI SD. Subjects in this study were the sixth grade students SDN 001 Bangun Purba active 24 people. Data collection at present uses both test and non-test techniques. Parameters used are Student Outcomes Includes learning activities and student learning outcomes. The results showed that the use of inquiry method was better (7,46) than did not use inquiry method (5,7). It needs to be done to add time by reducing the time is not too large points.